Regional Income Inequality in Lithuania - Laskiene, Daiva; Pekarskiene, Irena; Kontautiene, Rima (Economy of Regions, 2020)
The problem of income inequality is globally relevant, receiving the attention of both scientists and politicians. Lithuania as a small country has made significant progress in approaching the standard of living in Western Europe. However, there are still differences in economic growth between separate population groups. Thus, the problem of income inequality remains very acute. Currently, researchers are widely discussing the risk of income inequality to the country’s society by analysing its causes and proposing various solutions. Although scientific debates address income inequality across regions, such studies are often limited to examples of large countries. Meanwhile, there is a lack of studies on regional income inequality in small countries, so the question of whether a small country is characterised by regional income inequality remains open. This research aims to examine the level of regional income inequality in Lithuania. We hypothesised that Lithuania has a high level of regional income inequality and this is one of the causes of the high income inequality in the whole country. To estimate regional income inequality, we used the most common measures: Gini coefficient, decile ratio, and the coefficient of variation. The analysis was performed at level 3 of the Nomenclature of Territorial Units for Statistics (NUTS), according to which Lithuania is divided into 10 administrative counties. For this research, we chose the indicators illustrating income per capita on various levels, i.e., gross domestic product (GDP) per capita, average disposable household income per capita, and gross hourly wages, as the various types of income can be used. For the estimation of GDP per capita and average disposable household income, we analysed the data provided by the Lithuanian Department of Statistics (Statistics Lithuania) for 2014–2017. Due to a lack of data to estimate gross hourly wages, we examined the statistical data from the Lithuanian Department of Statistics for 2014. The results show that the hypothesis has not been confirmed. According to the research results, there is a small distribution of income between different regions of a small economy, although the level of economic development of different regions differs. The study findings are important not only from an academic perspective for identifying the causes of income inequality and raising questions for further research, but also for regional economic policy makers. The obtained results show that decisions related to a more equal distribution of income in Lithuania as a small country are determined not only by the specificity of its regions but also by the general trends of the country.